Synthesis, characterization and corrosion inhibitive ability of composites silica – polypyrrole - Hai Van, Vu Thi; Nam, Pham Thi; Thom, Nguyen Thi; Phuong, Nguyen Thu; Xuan Hang, To Thi; Mai Thanh, Dinh Thi (Vietnam Journal of Chemistry, 2017)
Composites silica/polypyrrole (SiO2/PPy) were synthesized by in-situ, using FeCl3 as oxidant, the quantity of silica is varied from 0.15 g, 0.3 g, 0.45 g to 0.6 g (SP1, SP2, SP3 and SP4, respectively). The morphologies and characterizations of composites were evaluated by FT-IR, EDX, SEM, TEM and TGA. EDX result indicated that the percentage of silicon increase from 20.48 to 28.14 % when the quantities of silica in initial mixture increase. Carbon steel were coated with polyninylbutyral (PVB) resin and PVB coatings containing 10 % SP1, SP2, SP3 and SP4 by spin coating technique. Corrosion protection performance of PVB coating containing SiO2/PPy was evaluated by measurement of OCP and potentiodynamic polarization. The results shows that the SiO2/PPy in PVB coating has corrosion inhibitive ability for carbon steel, it can shift the potential of steel into anode areas and reduce the corrosion current density more than 100 times. Keywords. Composite silica-polypyrrrole, corrosion inhibitive ability, corrosion performance.